Limitations of Postless Hip Arthroscopy for a Patient with Coxa Profunda: A Case Report. Issue 1 (January 2021) - Meek, Wendy M.; Abraham, Paul F.; Kucharik, Michael P.; Martin, Scott D.
Abstract : Case: A 27-year-old man with coxa profunda and a right acetabular labral tear presented for surgical re-evaluation after a postless arthroscopic labral repair was attempted at an outside institution and aborted because of inadequate distraction during portal placement. Arthroscopic labral repair with a perineal post was subsequently performed without complications. Conclusion: Indications and limitations of postless hip distraction are seldom discussed in the literature. This report examines possible limitations of postless hip distraction for a patient with coxa profunda. Careful radiographic evaluation of hip anatomy may be essential for patients with deep hip sockets to determine the best-suited distraction technique.